Pengaruh Ukuran Perusahaan, Struktur Modal, Profitabilitas Terhadap Kualitas Laba pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Reisha Putri Nabila; Dwi Susilowati; Winda Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Reisha Putri Nabila (2026). The Effect of Company Size, Capital Structure, and Profitability on Earnings Quality in Food and Beverage Subsector Companies Listed on The Indonesia Stock Exchange. Supervisors : Ms. Dwi Susilowati and Ms. Winda Lestari. The purpose of this study is to the determine the effect of company size, capital structure, and profitability on earnings quality in food and beverage subsector companies listed on the Indonesia Stock Exchange. This study used quantitative research with multiple linear regression analysis. This study used sample 0f 16 companies. The test used to validate this study were the classical assumption test, consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation. Multiple linear regression analysis and ANOVA tests, consisting of the correlation coefficient (R), the coefficient of determination (), and the F-statistic test, were also used. Hypothesis testing consisted of the t-test. The test results show that company size and capital structure do not have a significant effect on earnings quality, while profitability has a significant influence on earnings quality.